Studying radiation hardness of a cadmium tungstate crystal based radiation detector; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Shtein M. M. Mikhail Mikhailovich; Smekalin L. F. Leonid Fedorovich; Stepanov S. A. Sergey Aleksandrovich; Zatonov I. A. Ivan Andreevich; Tkacheva T. V.; Usachev E. Yu. (2016, 2016)
Title screen